Correlation of Grading of Esophageal Varices with Child Turcotte Pugh Class in Patients of Liver Cirrhosis - Shrestha, Anil; Khadka, Dipendra; Shrestha, Richa (Journal of Nepalgunj Medical College, 2018)
Background: Majority of cirrhotic patients develop  varices over their lifetime and it is anticipated that roughly one third of varices will develop bleeding. Child Turcotte Pugh (CTP) class predicts the risk of variceal bleeding and has been used as a prognostic tool inpatients of liver cirrhosis.Objective: To correlate grade of esophageal varices in Upper Gastrointestinal endoscopy with Child Turcotte Pugh class in patients of liver cirrhosis.Material and method: This is a cross sectional descriptive study conducted in thedepartment of medicine of NGMCTH, Kohalpur between December 2017 to November 2018. A total of 97 patients were included inthe study who were diagnosed as cirrhosis of liver clinically and radio logically. Patient were classified into CTP class A, B and According to CTP score. UGI endoscopy was performed and endoscopic grading of esophageal varices were correlated with CTP classand the data were recorded and analysed.Result: Mean of patients was 50 years. Among 97 patients, 30 (30.9%) were in CTP class A,30 (30.9%) in CTP class B and 37 (38.1%) were in CTP class C. 25 (25.8%) had small varices, 50 (51.5%) had large varices with red colorsign, 20 (20.6%) had large varices without red color sign and 2 (2.1%) had no varices. Most of the patients in CTP class B and C hadlarge varices with red color sign whereas CTP class A had small varices.Conclusion: The cirrhotic patients in CTP class B and C havelarge varices with red color sign and have more chances of bleeding. Hence, routine screening is indicated to determine the presenceof varices. Porphylactic therapy after identifying large varices will decrease the incidence of bleeding leading to reduction inmortality rate.